TINJAUAN LITERATUR MENGENAI PENGARUH PEMBELAJARAN MUSIK TERHADAP KETERAMPILAN SOSIAL SISWA SEKOLAH DASAR - Jonatan Fernando Silaban; Endang M Kurnianti, Susi Winarni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to review various literature discussing the impact of music education on the social skills of elementary school students. Music education is believed to have a positive effect on character development by enhancing students’ communication skills, empathy, cooperation, and self-regulation. This review adopts a literature study approach, analyzing eight national scholarly articles relevant to the topic. The articles were selected based on topic relevance, data completeness, and their contribution to explaining the relationship between music learning and social development in elementary-aged children. The findings indicate that music serves as an effective medium for social interaction. Collective musical activities such as group singing, ensemble instrument playing, and performing arts can foster active participation, empathy, tolerance, and the development of both verbal and nonverbal communication skills. Moreover, music education contributes to the development of self-discipline, responsibility, and appreciation for cultural diversity. Thus, music learning not only influences aesthetic aspects but also plays a significant role in character education and the social development of children. These findings reinforce the importance of integrating music into elementary education curricula as a holistic learning strategy. The study recommends further research exploring the specific effects of different types of musical activities on various dimensions of students’ social skills.